Pembrolizumab monotherapy for untreated PD-L1-Positive non-small cell lung cancer in the elderly or those with poor performance status: A prospective observational study - Shiotsu, Shinsuke; Yoshimura, Akihiro; Yamada, Tadaaki; Morimoto, Kenji; Tsuchiya, Michiko; Yoshioka, Hiroshige; Hiranuma, Osamu; Chihara, Yusuke; Yamada, Takahiro; Hasegawa, Isao; Ohta, Takahiro; Takeda, Takayuki; et al. (Frontiers in Oncology, 2022)
Objectives: We investigated the efficacy and safety of pembrolizumab monotherapy as first-line treatment for poor Eastern Cooperative Oncology Group performance status (PS) and elderly patients with programmed cell death-ligand 1 (PD-L1)-positive advanced non-small cell lung cancer (NSCLC). We also investigated clinical prognostic factors for the efficacy of pembrolizumab monotherapy, based on patient characteristics. Materials and Methods: In this prospective observational study, PS-2 and elderly NSCLC patients with PD-L1 tumor proportion score (TPS) ≥1% who received first-line pembrolizumab monotherapy, from October 2019 to March 2021, at 10 institutions in Japan were enrolled. Patients judged eligible by their physicians for combined chemotherapy and PD-1/PD-L1 inhibitors as first-line treatment were excluded. Clinicopathological characteristics and adverse events were investigated for correlation with clinical outcomes. Results: Forty patients were enrolled in the study. The median progression-free survival (PFS) of patients with PS 2 and those aged ≥ 75 years were 4.4 (95% confidence interval [CI]: 0.9–14.4) months and 5.3 (95% CI 2.9–9.4) months, respectively. The median overall survival (OS) of patients with PS 2 and those aged ≥ 75 years were 11.6 (95% CI: 1.4–not evaluable [NE]) months and 11.6 (95% CI 7.4–18.1) months, respectively. Immune-related adverse events (irAEs) were observed in 19 patients; 6 patients had severe irAEs of Common Terminology Criteria for Adverse Events (CTCAE) Grade 3 or higher. Patients who achieved stable disease or better, had a statistically significant increase in PFS (p < 0.001) and OS (p < 0.001); those who experienced irAEs had a significant increase in PFS (p = 0.027). In the multivariate analysis, the acquisition of disease control with pembrolizumab monotherapy was an independent prognostic factor for PFS and OS. Conclusion: Pembrolizumab monotherapy was relatively effective and tolerable as a first-line treatment for patients with PD-L1-positive advanced NSCLC who had poor PS or were elderly. Our results suggest that disease control might be an independent prognostic factor for PFS and OS in this population. (UMIN000044052 https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000050176)